PENYELESAIAN SENGKETA DENGAN ARBITRASE SECARA ONLINE DI BANI PADA MASA PANDEMI COVID-19 - Brian Austin Mauritz; Heru Suyanto (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
Globalization is something that cannot be avoided by humans in the world, including Indonesia. It can be said that because in fact, people's life in Indonesia has entered the digital era. This is due to technological advances and the use of the internet that make it easier for people to carry out their activities in any field. However, it is likely that a problem or dispute will occur due to the legal relationship that occurs online. With the existence of these disputes, the number of disputes that must be resolved becomes large and still must obtain a good resolution legally as well as face-to-face between the parties and the third party or the judge. Given the increasingly sophisticated technology, it does not rule out that technology or social media can be used to resolve a dispute or what is often referred to as Online Dispute Resolution (ODR) and online arbitration is included in it. Online arbitration was indeed carried out during the current Covid-19 pandemic. Therefore, the author wants to examine how certainty or legal basis and how to proceed online arbitration